The hydrodynamics of rowing propulsion: An experimental study - Grift, E. J. (Delft University of Technology, 2020)
The aim of this thesis is to analyse the hydrodynamics of rowing propulsion and to enhance this propulsion. This requires to have insight in both the flow phenomena and the generated hydrodynamic forces. In (competitive) rowing athletes generate a propulsive force by means of a rowing oar blade. During propulsion the oar blade is submerged close to the surface and the athlete exerts a force on the handle of the oar. This causes a reaction force fromthe water at the other end of the oar, the oar blade, which together with the force at the handle generates the propulsive force at the oar lock, the pivot point on the boat. For optimal performance it is essential to maximise the propulsion caused by this hydrodynamic reaction force at the blade. To achieve this, understanding of the flow field around the oar blade during this propulsive phase is vital. In chapter 2 the results are presented on the drag on, and the flow field around, a submerged rectangular normal flat plate, which is uniformly accelerated to a constant target velocity along a straight path. The plate aspect ratio is chosen to be AR = 2 to resemble an oar blade in (competitive) rowing. The plate depth, i.e. the distance from the top of the plate to the air-water interface, the plate acceleration and the plate target velocity are varied, resulting in a plate width based Reynolds number of 4£104 · Re · 8£104. In the analysis three phases are distinguished; (i) the acceleration phase during which the plate drag is increased, (ii) the transition phase during which the plate drag decreases to a constant steady value upon which (iii) the steady phase is reached. The plate drag force is measured as function of time which showed that the steady-phase plate drag at a depth of 1/5 plate height (20 mm depth for a plate height of 100 mm) increased by 45% compared to the plate top at the surface (0mm). Also, it is shown that the drag force during acceleration of the plate increases over time and is not captured by a single added mass coefficient for prolonged accelerations. Instead, an entrainment rate is defined that captures this behaviour. The formation of starting vortices and the wake development during the time of acceleration and transition towards a steady wake are studied using hydrogen bubble flow visualisations and particle image velocimetry. The formation time, as proposed by Gharib et al. (J. Fluid Mech., vol. 360, 1998, pp. 121-140), appears to be a universal time scale for the vortex formation during the transition phase. These findings serve as the basis for defining a best practice during the start of a rowing race as described in chapter 4. In chapter 3 the results are presented of experiments in which the flow around a realistic rowing oar blade, in combination with realistic kinematics, was measured using concurrent force measurements and PIV measurements. The aim of these experiments is to identify which flow phenomena govern rowing propulsion and subsequently adjust the oar blade configuration to optimise rowing propulsion. The oar blade moves along a cycloidal path, and due to the large accelerations and decelerations replicating the oar blade path is all but trivial. The oar blade and kinematics are scaled by a factor of 0.5 due to limitations of the experimental set-up. The flow field around the oar blade during the drive phase is measured and several flow phenomena such as the generation of leading and trailing edge vortices are linked to the generation of lift and drag, which both contribute to rowing propulsion. The oar blade performance is defined as the energetic and impulse efficiencies ´E and ´J , where the latter can be seen as the alignment of the generated impulse with the propulsive direction. It is found that when using a standard configuration of a rowing oar blade, the generated impulse is not aligned with the propulsive direction. This suggests that the propulsion is not optimal. By adjusting the angle at which the blade is attached to the oar an optimal oar blade angle was found (¯ = 15°) that aligns the generated impulse with the propulsive direction. At this angle the generation of leading and trailing edge vortices changes such that the overall hydrodynamic efficiency of the propulsion is optimised.Die Hydrodynamik des Vortriebs im Rudern: Eine experimentelle Studie